2016
DOI: 10.1109/tnet.2014.2360849
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Placement for Barrier Coverage in Bistatic Radar Sensor Networks

Abstract: By taking advantage of active sensing using radio waves, radar sensors can offer several advantages over passive sensors. Although much attention has been given to multistatic and multiple-input-multiple-output (MIMO) radar concepts, little has been paid to understanding radar networks (i.e., multiple individual radars working in concert). In this context, we study the coverage problem of a bistatic radar (BR) sensor network, which is very challenging due to the Cassini oval sensing region of a BR and the coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 28 publications
(78 reference statements)
0
28
0
Order By: Relevance
“…One of the main objectives of vulnerability detection and assessment is to analyze and understand various security risks that may exist in the whole system development process, and to provide scientific basis and intention for how to protect the security and development of the whole system. The whole system vulnerability here can be just one device as a service, or just the device stored on the network as a computer, or the entire computer network [11][12]. shows an example of an attack tree in which the attacker's goal is to get a free lunch.…”
Section: ) Network Unit Vulnerabilitymentioning
confidence: 99%
“…One of the main objectives of vulnerability detection and assessment is to analyze and understand various security risks that may exist in the whole system development process, and to provide scientific basis and intention for how to protect the security and development of the whole system. The whole system vulnerability here can be just one device as a service, or just the device stored on the network as a computer, or the entire computer network [11][12]. shows an example of an attack tree in which the attacker's goal is to get a free lunch.…”
Section: ) Network Unit Vulnerabilitymentioning
confidence: 99%
“…Sobhani et al proposed a tracking algorithm based on low-complexity particle filtering specifically tailored to radar sensor networks with one transmitter and several receivers [23]. Through studying the coverage problem of a bistatic radar sensor network, Gong et al reported valuable insights into the placement of bistatic radars for barrier coverage [24]. Liang and Cheng proposed a knowledge-based persistent sensor network for estimating parameters in target radar cross section [25].…”
Section: Microstrip Antenna Designmentioning
confidence: 99%
“…Barrier coverage problem has been extensively studied in [4,5,7,10,11,14,18,19]. A centralized optimal algorithm using sleep-wakeup model is proposed in [10] to achieve globally strong barrier coverage.…”
Section: Related Workmentioning
confidence: 99%